Predicting brain-age from multimodal imaging data captures cognitive impairment. - Liem, F.; Varoquaux, G.; Kynast, J.; Beyer, F.; Kharabian Masouleh, S.; Huntenburg, J. M.; Lampe, L.; Rahim, M.; Abraham, A.; Craddock, R. C.; Riedel-Heller, S.; Luck, T.; et al. (Neuroimage, 2017)
The disparity between the chronological age of an individual and their brain-age measured based on biological information has the potential to offer clinically relevant biomarkers of neurological syndromes that emerge late in the lifespan. While prior brain-age prediction studies have relied exclusively on either structural or functional brain data, here we investigate how multimodal brain-imaging data improves age prediction. Using cortical anatomy and whole-brain functional connectivity on a large adult lifespan sample (N=2354, age 19-82), we found that multimodal data improves brain-based age prediction, resulting in a mean absolute prediction error of 4.29 years. Furthermore, we found that the discrepancy between predicted age and chronological age captures cognitive impairment. Importantly, the brain-age measure was robust to confounding effects: head motion did not drive brain-based age prediction and our models generalized reasonably to an independent dataset acquired at a different site (N=475). Generalization performance was increased by training models on a larger and more heterogeneous dataset. The robustness of multimodal brain-age prediction to confounds, generalizability across sites, and sensitivity to clinically-relevant impairments, suggests promising future application to the early prediction of neurocognitive disorders.
Keywords: Adult; Aged; Aged, 80 and over; Brain/*diagnostic imaging/*growth & development; Cerebral Cortex/diagnostic imaging/growth & development; Cognitive Dysfunction/*diagnostic imaging/psychology; Female; Head Movements; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Models, Neurological; Multimodal Imaging/*methods; Neuropsychological Tests; Predictive Value of Tests; Reproducibility of Results; Young Adult